The Influence of Innovative Teaching Methods on Students’ Learning - Ingale, Sanjaykumar; Gavali, Pankaj B. (Asian Journal of Science and Applied Technology, 2021)
The emphasis of outcome-based education has changed from teaching to learning. Stakeholders are calling for high-quality education. In the evaluation and accreditation process, more emphasis is placed on the teaching and learning process. Students' knowledge and skill set are becoming increasingly crucial. As a result, it is critical for a teacher to use an original technique when presenting the course. It is necessary to categorise the learners in order to construct these techniques. This article focuses on the categorization of SY B Tech learners at the start of the manufacturing processes course. The strategies that must be used to accommodate these various sorts of learners are also explored. Aside from typical teaching methods, think-pair-share, flipped classroom, and blended learning tactics were employed. The criterion for evaluating these techniques has been developed. It is proposed that these tactics be used to different courses for different programmes to confirm the outcomes or, if any, variances before being implemented across institutions/universities.